2019
DOI: 10.31533/pubvet.v13n8a386.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and profile of those infected in schistosomiasis in the State of Alagoas in 2016 to 2017

Abstract: Licenciamento: Este artigo é publicado na modalidade Acesso Aberto sob a licença Creative Commons Atribuição 4.0 (CC-BY 4.0), a qual permite uso irrestrito, distribuição, reprodução em qualquer meio, desde que o autor e a fonte sejam devidamente creditados.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
0
1
1
Order By: Relevance
“…In Alagoas, studies have shown that schistosomiasis persists as a rural endemic in areas of low prevalence 17 , 18 , which differs from the data found in this study. On the other hand, a high prevalence has already been found in urban areas of two high prevalence cities in the state 19 , but the authors of the study did not perform the investigation, at the time, in the rural area of the municipality.…”
Section: Discussioncontrasting
confidence: 99%
“…In Alagoas, studies have shown that schistosomiasis persists as a rural endemic in areas of low prevalence 17 , 18 , which differs from the data found in this study. On the other hand, a high prevalence has already been found in urban areas of two high prevalence cities in the state 19 , but the authors of the study did not perform the investigation, at the time, in the rural area of the municipality.…”
Section: Discussioncontrasting
confidence: 99%
“…Na periferia, as precárias condições de saneamento básico aliadas à presença de pessoas parasitadas resultam na contaminação de corpos d'água naturais e consequentemente dos hospedeiros intermediários do parasita, instalando pontos de contaminação, promovendo assim o ciclo do parasita e consequentemente a doença (Barbosa, et al, 2010;Jordão, et al, 2014;Oliveira, et al, 2018). Esta associação de condições justificam a ocorrência da esquistossomose mansônica, associada a fatores de ordem social, econômica, cultural e política (Santos, et al, 2019;Silva, et al, 2020).…”
Section: Fonte: Sinan (2021)unclassified